Reconstructive surgery to preserve ankle function in a 5-year-old girl with bilobed distal tibia in an unclassified case of tibial hemimelia: a case report - Alireza Ghaznavi; Miad Nosratpour; Seyed Mohammadmisagh Moteshakereh; Ava Parvandi; Shayan Amiri (Journal of Medical Case Reports)
Abstract Background Tibial hemimelia is an uncommon congenital abnormality ranging from a solitary skeletal deformity to associations with other syndromes. Despite Paley et al.’s detailed classification of tibial hemimelia, some unique sporadic cases still do not fit within this system. In 2021, Chong et al. proposed the most recent surgical approach based on the Paley classification, which inspired cases such as ours. Case presentation This case study presents a novel case of tibial hemimelia characterized by a bilobed distal tibia, a shortened first ray, and an equinovarus deformity in a 5-year-old Iranian (Lur) girl. She experienced pain, limping, and cosmetic concerns. The surgical procedures performed for preservation are thoroughly described and discussed. Conclusion This case has been identified as a new variant of Paley type 2. A staged approach to reconstructive surgery was advocated to ensure the preservation of ankle function and to prevent extreme procedures such as amputation. The most recent follow-up demonstrated promising results.